2014
DOI: 10.19030/jabr.v30i2.8411
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Talent Management In Enhancing Organizational Reputation: An Empirical Study On The Jordanian Telecommunications Companies

Abstract: <p>The research explores the effect of talent management on improving organization reputation through exploring the relationship between talent management variables (discover, inspire, transform) and reputation variables (self-enhancement, self-verification, frequency of interaction). The first part of the project introduces a literature review of the importance talent management and reputation and their role on dealing with the competitive market. Next, the paper introduces the variables and the theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This is consistent with the study of (Egerova, et al, 2013) According to these results level of application of Talent Management strategies in the airlines in Egypt is to some exent whis is consistent with study of (Aljarrah, et al, 2015); which found that level of application of Talent management strategies in Official Jordanian Universities is medium. And it is also consistent with the study of (Salih & Alnaji, 2014); which found that talent management is still below the level of ambition showing that Jordanian Telecommunications Companies need to pay attention to talent management if they wish to maintain proper customer interaction. 6-5 Interest of airlines in measuring their competitiveness and identifying factors that affect them 6-5-1 Interest of airlines sample to measure their competitiveness: 16) that airlines sample's Interest to measure their competitiveness comes at an average (2.56) towards yes, with a standard deviation (0.558).…”
Section: -4-4 Airlines Sample's Quest For Talent Developmentsupporting
confidence: 88%
“…This is consistent with the study of (Egerova, et al, 2013) According to these results level of application of Talent Management strategies in the airlines in Egypt is to some exent whis is consistent with study of (Aljarrah, et al, 2015); which found that level of application of Talent management strategies in Official Jordanian Universities is medium. And it is also consistent with the study of (Salih & Alnaji, 2014); which found that talent management is still below the level of ambition showing that Jordanian Telecommunications Companies need to pay attention to talent management if they wish to maintain proper customer interaction. 6-5 Interest of airlines in measuring their competitiveness and identifying factors that affect them 6-5-1 Interest of airlines sample to measure their competitiveness: 16) that airlines sample's Interest to measure their competitiveness comes at an average (2.56) towards yes, with a standard deviation (0.558).…”
Section: -4-4 Airlines Sample's Quest For Talent Developmentsupporting
confidence: 88%
“…In addition to ambidexterity, many other fundamental aspects, such as strategic agility [1], [2], [18], operational agility [19], [20], and an agile organizational structure [21] have been found in companies from the insurance and banking industry. However, changing people's mindsets and cultures is known as one of the most challenging aspects of agile transformations [10], [18], [19], [22], as it is an endeavour that can only be accomplished in a top-down and bottom-up effort to reach all levels of the organization [2], [23], [24].…”
Section: Agile In the Insurance And Banking Industrymentioning
confidence: 99%
“…Today, the increasing uncertainty and instability brought by new competitors and ways of doing business make it crucial for traditional companies to become more agile and able to act fast on consumer needs and expectations [1], [2]. However, this is traditionally not an easy task for many insurance companies as they typically operate with functional and hierarchical organizations that only enable them to succeed in more stable environments.…”
Section: Introductionmentioning
confidence: 99%
“…The construct talent management as conceptualized today was popularized by McKinsey Group statement "war for talent" (Beardwell & Claydon, 2007;Tarique & Schuler, 2010;Simonton, 2011). Salih and Alnaji (2014) state that it is not easy to define TM since the term is interchangeably used to describe processes and outcomes. Rathod (2014) defines TM as talent while Al-Qarioti (2016) argue that talent and TM mean the same depending on the type of organization strategies and the environment.…”
Section: Talent Managementmentioning
confidence: 99%